HIC1 Tumor Suppressor Loss Potentiates TLR2/NF-κB Signaling and Promotes Tissue Damage-Associated Tumorigenesis - Janeckova, Lucie; Pospichalova, Vendula; Fafilek, Bohumil; Vojtechova, Martina; Tureckova, Jolana; Dobes, Jan; Dubuissez, Marion; Leprince, Dominique; Baloghova, Nikol; Horazna, Monika; Hlavata, Adela; Stancikova, Jitka; et al. (Molecular cancer research, 2015)
UNLABELLED: Hypermethylated in cancer 1 (HIC1) represents a prototypic tumor suppressor gene frequently inactivated by DNA methylation in many types of solid tumors. The gene encodes a sequence-specific transcriptional repressor controlling expression of several genes involved in cell cycle or stress control. In this study, a Hic1 allele was conditionally deleted, using a Cre/loxP system, to identify genes influenced by the loss of Hic1. One of the transcripts upregulated upon Hic1 ablation is the toll-like receptor 2 (TLR2). Tlr2 expression levels increased in Hic1-deficient mouse embryonic fibroblasts (MEF) and cultured intestinal organoids or in human cells upon HIC1 knockdown. In addition, HIC1 associated with the TLR2 gene regulatory elements, as detected by chromatin immunoprecipitation, indicating that Tlr2 indeed represents a direct Hic1 target. The Tlr2 receptor senses "danger" signals of microbial or endogenous origin to trigger multiple signaling pathways, including NF-κB signaling. Interestingly, Hic1 deficiency promoted NF-κB pathway activity not only in cells stimulated with Tlr2 ligand, but also in cells treated with NF-κB activators that stimulate different surface receptors. In the intestine, Hic1 is mainly expressed in differentiated epithelial cells and its ablation leads to increased Tlr2 production. Finally, in a chemical-induced mouse model of carcinogenesis, Hic1 absence resulted in larger Tlr2-positive colonic tumors that showed increased proportion of proliferating cells. IMPLICATIONS: The tumor-suppressive function of Hic1 in colon is related to its inhibitory action on proproliferative signaling mediated by the Tlr2 receptor present on tumor cells.
Keywords: epitelové buňky; nádorové buněčné linie; signální transdukce; Up-Regulation; Intestines; myši transgenní; upregulace; azoxymethan; Disease Models, Animal; NF-kappa B; Epithelial Cells; Signal Transduction; Carcinogenesis; Mice; Cell Proliferation; Cell Line, Tumor; Gene Knockdown Techniques; střeva; nádory tračníku; modely nemocí na zvířatech; nádorové supresorové proteiny; zvířata; Humans; transkripční faktory Krüppel-like; Kruppel-Like Transcription Factors; Toll-Like Receptor 2; Colonic Neoplasms; Tumor Suppressor Proteins; toll-like receptor 2; genový knockdown; síran dextranu; myši; proliferace buněk; Azoxymethane; karcinogeneze; Mice, Transgenic; lidé; Dextran Sulfate; Animals